The rewrite [videorecording (DVD)] - Grant, Hugh; Tomei, Marisa; Simmons, J. K.; Janney, Allison (Image Entertainment, 2015)
Screenwriter Keith Michaels was once on top of the world. Now he's divorced, broke, approaching fifty, and hasn't written a hit film in years. So when a university in the quiet town of Binghamton asks him to teach a course in screenwriting, Keith can't say no. His attitude slowly begins to change once he gets to know his students, including Holly, a single mom looking to start a new chapter in life.